Comparative validity of microalbuminuria versus clinical mortality scores to predict pediatric intensive care unit outcomes - Shifa Nismath; Suchetha S. Rao; B.S. Baliga; Vaman Kulkarni; Gayatri M. Rao (The Korean Pediatric Society, 2020)
Background Predicting the prognosis of patients admitted to the pediatric intensive care unit (PICU) is very important in determining further management and resource allocation. The prognostication of critically ill children can be challenging; hence, accurate methods for predicting outcomes are needed. Purpose To evaluate the role of microalbuminuria at admission as a prognostic marker in comparison to standard Pediatric Risk of Mortality (PRISM) and Pediatric Logistic Organ Dysfunction (PELOD) mortality scores in children admitted to the PICU. Methods This cross-sectional study was conducted from January 2015 to October 2016. Eighty-four patients aged 1 month to 18 years admitted to the PICU of teaching hospitals for more than 24 hours were enrolled by convenience sampling method. Microalbuminuria was estimated by spot urinary albumin-creatinine ratio. PRISM and PELOD scores were calculated using an online calculator. Outcome measures were PICU length of stay, inotrope usage, multiorgan dysfunction, and survival. ACR was compared with mortality scores for predicting survival. Results Microalbuminuria was present in 79.8% with a median value of 85 mg/g (interquartile range, 41.5-254 mg/g). A positive correlation was found between albumin-creatinine ratio and PICU length of stay (P=0.013, r=0.271). Albumin-creatinine ratio was significantly associated with organ dysfunction (P=0.004) and need for inotropes (P=0.006). Eight deaths were observed in the PICU. The area under the curve for mortality for albumin-creatinine ratio (0.822) was comparable to that for PRISM (0.928) and PELOD (0.877). Albumin-creatinine ratio >109 mg/g predicted mortality with a sensitivity of 87.5% and specificity of 63.2%. Conclusion Microalbuminuria is a good predictor of PICU outcomes comparable with mortality scores.